Stacking Analysis of the Mastery of Science Concepts in the RADEC Learning Model for Grade IV Elementary Students - Nurul Istiqomah; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2023)
The study analyzes the mastery of science concepts in fourth-grade student' style material using the RADEC (Read, Answer, Discuss, Explain and Create) learning model. This study used a quantitative experiment, and the research method used was the One Group Pretest and Posttest with a sample of 29 students. Students will be given pretest questions first to find out student mastery of concepts in Style material, then given pre-leaming questions that are done outside of class hours and then create work. After working on pre-learning questions, students work on post-test questions to measure students succes in mastering the IPA concept on Style material. After participating in learning with the RADEC learning model, students experienced an increase to an outstanding category of 44.83, good at 48.28%, and enough of 6.90%. Logit values from the pretest and posttest can be used to quantify this rise. The findings demonstrated that studying with the RADEC model improved students' comprehension of science ideas for both low- and high-ability pupils